2015
DOI: 10.1590/s0100-204x2015000500001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and energy metabolism of Nile tilapia juveniles fed glycerol

Abstract: -The objective of this work was to evaluate the effect of inclusion of dietary glycerol in replacement to starch on the growth and energy metabolism of Nile tilapia juveniles. The experiment was carried out in a completely randomized design with four treatments (0, 5, 10, and 15% purified glycerol) and six replicates. Pelleted, isonitrogenous, and isocaloric diets were provided for 60 days. Growth performance parameters and muscle glucose and protein concentrations were not affected by dietary glycerol levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 20 publications
3
25
1
2
Order By: Relevance
“…Therefore, the substitution of corn by crude glycerol is feasible and does not affect the efficiency of feed utilization of the Nile tilapia in the fattening stage. Studies with the same species, at different stages, also showed the noneffect of glycerol on the FCR values (Neu et al, 2012b(Neu et al, , 2013Costa et al, 2015;Meurer et al, 2016). Fish survival was not influenced by the inclusion of crude glycerol in diets (Table 2), which agrees with the results of Li et al (2010), Neu et al (2013), Gonçalves et al (2015), Costa et al (2015), and Meurer et al (2016).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, the substitution of corn by crude glycerol is feasible and does not affect the efficiency of feed utilization of the Nile tilapia in the fattening stage. Studies with the same species, at different stages, also showed the noneffect of glycerol on the FCR values (Neu et al, 2012b(Neu et al, , 2013Costa et al, 2015;Meurer et al, 2016). Fish survival was not influenced by the inclusion of crude glycerol in diets (Table 2), which agrees with the results of Li et al (2010), Neu et al (2013), Gonçalves et al (2015), Costa et al (2015), and Meurer et al (2016).…”
Section: Resultssupporting
confidence: 82%
“…Other studies also found no variation for the growth parameters of juvenile Nile tilapia, when up to 100 g kg -1 glycerol (Neu et al, 2013), or 150 g kg -1 glycerol (Costa et al, 2015) was added to their diets, namely in the final mean weight and in weight gain. Up to 110 g kg -1 glycerol can be included in diets of Nile tilapia in the post larvae stage, without affecting the final weight, according to Meurer et al (2016).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…A inclusão de glicerina bruta nas dietas influenciou a glicemia e a concentração plasmática de triglicerídeos de modo contrário ao relatado para juvenis de tilápia-do-nilo (NEU et al, 2013;COSTA et al, 2015). Para o bagre-docanal, a glicose sanguínea foi significantemente maior em peixes alimentados com 5% de glicerol que para os peixes alimentados com as outras dietas (LI et al, 2010).…”
Section: Variávelunclassified
“…Apesar de até 10% de glicerol na dieta não ter prejudicado o desempenho produtivo e a saúde de juvenis (NEU et al, 2013), o melhor ganho de peso foi alcançado com sua inclusão em 5,9% da dieta (GONÇALVES et al, 2015). Além disso, níveis acima de 10% o caracterizaram como nutriente lipogênico (COSTA et al, 2015).…”
Section: Introductionunclassified